In silico analysis of compounds characterized from ethanolic extract of Cucurbita pepo with NF-κB-inhibitory potential - Solomon O. Rotimi; Oluwakemi Anuoluwapo Rotimi; Olawole O. Obembe (Bangladesh Pharmacological Society, 2014)
NF-κB controls cellular growth properties of cells and its regulation is key to the management of disease like cancer. Although plant-derived bioactives have been reported to inhibit NF-κB, there is limited knowledge on the interactions between the phytochemicals and NF-κB. In this study, we identified the phytochemicals in ethanolic extract of Cucurbita pepo using Gas Chromatography-Mass Spectroscopy technique and used in silico approach to understand the interaction between the identified phytochemicals and NF-κB using Molegro Virtual Docker. The docking algorithm showed that nine phytochemicals fit well into the pocket on NF-κB. Our analysis showed that Lys144 is a prominent residue by involving in the binding of 9-octadecenoic acid (Z)-, methyl ester, hexadecanoic acid, methyl ester and octadecanoic acid, methyl ester with the moldock score of -55.5264, -57.4634 and -61.1258 respectively. Hence, the binding of these phytochemicals to NF-κB could be responsible for the anti-inflammatory and anti-cancer property of C. pepo.